Perancangan Aplikasi Rental Skuter Malioboro Berbasis Mobile Menggunakan Metode User Centered Design (UCD) - Bandrio Ilham Novanto; Sulistyo Dwi Sancoko (Journal of Information System Research (JOSH), 2025)
Along Malioboro street, there are electric scooter rental services that make it easier for tourists to explore the surrounding area. By renting an electric scooter, visitors can enjoy the nighttime atmosphere with a gentle breeze and a beautiful view of the city lights. This service is in high demand, especially by young people, as it provides a unique and fun traveling experience. Although the scooter rental service in Malioboro provides convenience for tourists, there are some problems faced in its implementation. One of the main problems is the absence of a dedicated platform for scooter rental. Travelers can only rent directly, so there is often a scramble. In addition, some users leave the scooters carelessly on sidewalks or pedestrian areas, thus disrupting pedestrian comfort and accessibility. To solve the problem of tourists renting scooters in Malioboro, the service provider provides a rental system that includes a short training on riding rules and safety before users rent the scooter in the form of a mobile application. This application was developed using the User Centered Design method by focusing on user problems and needs. Kotlin and MySQL were also used in its development, while testing was carried out using the Black Box Testing method. Based on the testing conducted, it can be concluded that the application can run well and produce a percentage of 91.6%. The resulting application can handle problems that exist in Scooter Rental in Malioboro such as ordering scooters and information on their use.